Uma reflexão sobre as representações do eu e os elementos antilíricos na poética de Sebastião Uchoa Leite - Ludimila Luchini Noventa (2024)
The main objective of this dissertation is to study the representations of the self composed by means of antilyric elements in the poetry of Sebastião Uchoa Leite. Here, the study focuses on the unique way in which the poet establishes a new means of lyrical repositioning of the self and subjectivity, revealing a complex process of poetic elaboration. The dissertation is divided into four chapters, which are dedicated, firstly, to understanding the context of the poet's production and the theoretical framework that reading his poetry implies; and the following sequence of chapters addresses the analysis of his poems and deals with three main groupings of forms of representation of the self, namely: a reflective self, an anti-self and a self of masks. In this journey, we understand the ways in which the self is relocated, in his poetry, through the modern anti-lyric perspective. Constant rationality, distrust, distancing and contrariety make up the representation of an insistent self, characterized by inventive methods that associate lyrical resistance with the lessons of the avant-garde that preceded it.